Statin therapy and mortality in critically ill heart failure patients: Insights from a triangulated real-world design study - Li Wang; Yibing Wang (PLoS ONE, 2025)
This study is aimed to evaluate the association between statin therapy and intermediate-term survival in critically ill patients with heart failure (HF). Using a real-world retrospective cohort from the MIMIC-IV database, we assessed all-cause mortality at 90 and 180 days following ICU admission. To reduce confounding factors, we applied a triangulated analytic framework incorporating propensity score matching, inverse probability of treatment weighting and standardized mortality ratio weighting. Survival outcomes were additionally examined across different statin types, including atorvastatin, rosuvastatin, simvastatin and pitavastatin, using stratified Kaplan–Meier analysis. Among over 8,000 eligible patients, statin use during hospitalization was consistently associated with reduced mortality at both time points across all models. Stratified survival curves showed comparable trends among the different statin types. These findings suggest a potential class-wide survival benefit of statin therapy in the ICU setting for HF patients and highlight the need for further studies to determine whether specific statin selection offers additional clinical advantages.